Enhancing the hydrogen storage capacity of Pd-functionalized multi-walled carbon nanotubes - Singh, Priyanka; Kulkarni, Mukta V.; Gokhale, Suresh P.; Chikkali, Samir H.; Kulkarni, Chandrashekhar V. (Applied Surface Science, 2012)
We demonstrate that the hydrogen storage capacity of multi-walled carbon nanotubes can be enhanced by polyvinylpyrrolidone functionalization. The polyvinylpyrrolidone acts as a stabilizing agent for Pd-nanoparticles, reduces their size and facilitates their uniform and enhanced loading onto multi-walled carbon nanotubes. According to sorption studies, the polyvinylpyrrolidone capping and consequent nanostructural modification enables 2.3 times more hydrogen adsorption than mere Pd-functionalization of multi-walled carbon nanotubes. Corresponding morphological changes before and after polyvinylpyrrolidone capping, characterized using Raman Spectroscopy, X-ray diffraction, TEM and thermal analysis techniques, are also presented. The results contribute towards increasing the efficiency of hydrogen based sustainable energy sources. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Hydrogen based energy sources; Hydrogen storage capacity; Multiwalled carbon nanotubes; Pd functionalization; PVP capping

Insecticidal potential of defense metabolites from ocimum kilimandscharicum against helicoverpa armigera - Singh, Priyanka; Jayaramaiah, Ramesha H.; Sarate, Priya; Thulasiram, Hirekodathakallu V.; Kulkarni, Mahesh J.; Giri, Ashok P. (Plos One, 2014)
Genus Ocimum contains a reservoir of diverse secondary metabolites, which are known for their defense and medicinal value. However, the defense-related metabolites from this genus have not been studied in depth. To gain deeper insight into inducible defense metabolites, we examined the overall biochemical and metabolic changes in Ocimum kilimandscharicum that occurred in response to the feeding of Helicoverpa armigera larvae. Metabolic analysis revealed that the primary and secondary metabolism of local and systemic tissues in O. kilimandscharicum was severely affected following larval infestation. Moreover, levels of specific secondary metabolites like camphor, limonene and beta-caryophyllene (known to be involved in defense) significantly increased in leaves upon insect attack. Choice assays conducted by exposing H. armigera larvae on O. kilimandscharicum and tomato leaves, demonstrated that O. kilimandscharicum significantly deters larval feeding. Further, when larvae were fed on O. kilimandscharicum leaves, average body weight decreased and mortality the larvae increased. Larvae fed on artificial diet supplemented with O. kilimandscharicum leaf extract, camphor, limonene and beta-caryophyllene showed growth retardation, increased mortality rates and pupal deformities. Digestive enzymes of H. armigera - namely, amylase, protease and lipase- showed variable patterns after feeding on O. kilimandscharicum, which implies striving of the larvae to attain required nutrition for growth, development and metamorphosis. Evidently, selected metabolites from O. kilimandscharicum possess significant insecticidal activity.

Towards comprehension of complex chemical evolution and diversification of terpene and phenylpropanoid pathways in Ocimum species - Singh, Priyanka; Kalunke, Raviraj M.; Giri, Ashok P. (RSC Advances, 2015)
Ocimum species present a wide array of diverse secondary metabolites possessing immense medicinal and economic value. The importance of this genus is undisputable and exemplified in the ancient science of Chinese and Indian (Ayurveda) traditional medicine. Unlike several other plant species of Artemisia, Salvia, Catharanthus, Taxus, Mentha, etc. that are largely exploited, detailed characterization and identification of important metabolites from Ocimum species remained unexplored. Till date, most of the analyzed Ocimum species are predominantly rich in either phenylpropanoids or terpenoids. Metabolite data suggests domination of a unique set of signature compounds in all species. However, molecular pathways leading to the production, accumulation and metabolism of these compounds are poorly understood. The past few years have witnessed an upsurge in our understanding of the complex and intricately woven secondary metabolic pathways. Such information is generated through systematic analysis and correlation of metabolite profiling with transcriptomics data sets from different Ocimum species. The present review is aimed at integrating our current knowledge to understand the active secondary metabolic pathways, the key players in flux regulation including external stimuli, differential gene expression, transcription factors, microRNAs, enzyme promiscuity, etc. Extensive analysis of available data identifies events that may have contributed to evolve Ocimum species rich with a specific set of metabolites, thus, shedding light on pathway diversification. We believe that a better understanding of the multi-level regulation of intermediates and metabolites will help us harness the inherent diversity of Ocimum species optimally.

Potential dual role of eugenol in inhibiting advanced glycation end products in diabetes: proteomic and mechanistic insights - Singh, Priyanka; Jayaramaiah, Ramesha H.; Agawane, Sachin B.; Vannuruswamy, Garikapati; Korwar, Arvind M.; Anand, Atul; Dhaygude, Vitthal S.; Shaikh, Mahemud L.; Joshi, Rakesh S.; Boppana, Ramanamurthy; Kulkarni, Mahesh J.; Thulasiram, Hirekodathakallu V.; et al. (Scientific Reports, 2016)
Medicinally important genus Ocimum harbors a vast pool of chemically diverse metabolites. Current study aims at identifying anti-diabetic candidate compounds from Ocimum species. Major metabolites in O. kilimandscharicum, O. tenuiflorum, O. gratissimum were purified, characterized and evaluated for anti-glycation activity. In vitro inhibition of advanced glycation end products (AGEs) by eugenol was found to be highest. Preliminary biophysical analysis and blind docking studies to understand eugenol-albumin interaction indicated eugenol to possess strong binding affinity for surface exposed lysines. However, binding of eugenol to bovine serum albumin (BSA) did not result in significant change in secondary structure of protein. In vivo diabetic mice model studies with eugenol showed reduction in blood glucose levels by 38% likely due to inhibition of alpha-glucosidase while insulin and glycated hemoglobin levels remain unchanged. Western blotting using anti-AGE antibody and mass spectrometry detected notably fewer AGE modified peptides upon eugenol treatment both in vivo and in vitro. Histopathological examination revealed comparatively lesser lesions in eugenol-treated mice. Thus, we propose eugenol has dual mode of action in combating diabetes; it lowers blood glucose by inhibiting a-glucosidase and prevents AGE formation by binding to epsilon-amine group on lysine, protecting it from glycation, offering potential use in diabetic management.

Biosynthesis and tissue-specific partitioning of camphor and eugenol in Ocimum kilimandscharicum - Singh, Priyanka; Kalunke, Raviraj M.; Shukla, Anurag; Tzfadia, Oren; Thulasiram, V. Hirekodathakallu; Giri, Ashok P. (Phytochemistry, 2020)
In Ocimum kilimandscharicum, the relative volatile composition of camphor in leaves was as high as 55%, while that of eugenol in roots was 57%. These metabolites were differentially partitioned between the aerial and root tissues. Global metabolomics revealed tissue-specific biochemical specialization, evident by the differential distribution of 2588 putative metabolites across nine tissues. Next-generation sequencing analysis indicated differential expression of 51 phenylpropanoid and 55 terpenoid pathway genes in aerial and root tissues. By integrating metabolomics with transcriptomics, the camphor biosynthesis pathway in O. kilimandscharicum was elucidated. In planta bioassays revealed the role of geranyl diphosphate synthase (gpps) and borneol dehydrogenase (bdh) in camphor biosynthesis. Further, the partitioning of camphor was attributed to tissue-specific gene expression of both the pathway entry point (gpps) and terminal (bdh) enzyme. Unlike camphor, eugenol accumulated more in roots; however, absence of the eugenol synthase gene in roots indicated long distance transport from aerial tissues. In silico co-expression analysis indicated the potential involvement of ATP-binding cassette, multidrug and toxic compound extrusion, and sugar transporters in eugenol transport. Similar partitioning was evident across five other Ocimum species. Overall, our work indicates that metabolite partitioning maybe a finely regulated process, which may have implications on plant growth, development, and defense.
Keywords: Borneol dehydrogenase; Camphor; Eugenol; Geranyl diphosphate synthase; Lamiaceae; Metabolite partitioning; Metabolomics; Ocimum kilimandscharicum; Transcriptomics